Evolution of microstructure and texture in the stir zone of commercially pure titanium during friction stir processing. (March 2022) - Singh, Abhishek Kumar; Kaushik, Lalit; Singh, Jaiveer; Das, Hrishikesh; Mondal, Mounarik; Hong, Sung-Tae; Choi, Shi-Hoon
Highlights: The microstructure and texture in the SZ of FSPed CP-Ti were investigated. An equiaxed submicron grain microstructure was observed across the SZ, which was induced by dynamic grain refinement and supported by a multi-faceted DRX mechanism. An FEA-supported VPSC polycrystal model that featured Zener-Hollomon parameter dependent microscopic hardening and a DRX scheme was utilized. VPSC model successfully predicted the development of strong and heterogeneous fiber textures across the SZ. In-plane shear components of the velocity gradients (L12 and L21 ) were mainly responsible for the crystal rotation about the normal direction in the SZ. Abstract: The microstructure and texture in the stir zone (SZ) of friction-stir-processed (FSPed) commercially pure titanium (CP-Ti) were investigated via electron backscatter diffraction (EBSD), finite element analysis (FEA), and polycrystal modeling. The EBSD characterization elucidated the development of an equiaxed submicron grain microstructure across the SZ, which was induced by dynamic grain refinement and supported by a multi-faceted mechanism for dynamic recrystallization (DRX). FEA was used to theoretically explain the spatial and time dependence shown by the deformation history and to elucidate the distributions of temperature, strain, and strain rate that occur in CP-Ti during FSP. The deformation history results from FEA were further utilized as input for establishing a visco-plastic self-consistent (VPSC) polycrystal model that featured Zener-Hollomon parameter-dependent microscopic hardening and a DRX scheme to predict the texture evolution in FSPed material. The texture development in the SZ of FSPed material was highly dependent on the thermo-mechanical history of different zones of the FSPed CP-Ti. The combination of EBSD and VPSC modeling revealed a strong fiber texture in the SZ. Systems of prismatic and pyramidal slip and compression twinning appear to be the dominant deformation modes in the SZ. In-plane shear components of the velocity gradients (L12 and L21 ) are mainly responsible for the crystal rotation about the normal direction in the SZ. On the other hand, normal and other shear components did not appear to alter the crystal rotation but did affect the texture intensity, spread and symmetry.